De Hongaarse galeislaaf-predikanten en Nederland - Bujtás, László Zsigmond (Acta Neerlandica, 2026)
The Hungarian protestant ministers who had been baselessly charged in 1673 and 1674 by a special court at Pressburg with rebellion, treason and defamation of the Catholic Church were sentenced to death. Those who converted to Catholicism or promised to leave the country could escape. Those who persisted were sold at Naples to Spanish galleys as slaves. The ministers asked help, among others, from the Netherlands. As a result of efforts of many persons the States General instructed in November 1675 admiral Michiel de Ruyter to liberate the galley slaves. After their liberation in February 1676, they were in exile in Zürich. Eight of them visited the Netherlands in the autumn of that year to try to get diplomatic and financial support so that they could return to Hungary in order to continue their ministry. The Netherlands helped them a lot in both areas. Lots of books dealt with their story in the 17th and 18th centuries in the Netherlands. Later they became more and more part of the memory place ‘Michiel de Ruyter’.